Strwberry production from transplant fumigated with methyl bromide alternatives - Lopez Medina, J.=700 1 Lopez Aranda, J.M.; Medina, J.J.; Miranda, L.; Soria, C.
(En, Es)
Ilus., 20 ref.
Keywords: FRAGARIA VESCA; FUMIGACION DEL SUELO; BROMURO DE METILO; COMPOSICION QUIMICA; DICLOROPROPENO; VIVEROS; ESPAÑA; FRESON